(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
Due to the current revolution in quick technology use, which results in a decline in energy source, energy consumption is rising. The primary cause of this issue is the unchecked wasteful behavior of consumers when using electricity. The Rapid Application Development (RAD) model, Internet of Things (IoT) technology, the MQTT Dashboard application, AdaFruit IO software as a database of developed systems, a NodeMCU ESP8266 controller, and an ACS712 30A current sensor are all part of the methodology chosen to carry out this project. The ESP8266 NodeMCU microcontroller will interpret the data from the ACS712 current sensor and display it as a monitoring tool on the computer's AdaFruit IO software and the MQTT Dashboard app on the user's smartphone. This project's user-friendly features allow us to track the cost of electricity use over the course of a day and a month, regardless of where we are located. The advantages of this method can be summed up as being cost-effective, straightforward, and simple to maintain.